2012
DOI: 10.2164/jandrol.111.013888
|View full text |Cite
|
Sign up to set email alerts
|

Low Androgen Sensitivity Is Associated With Low Levels of Akt Phosphorylation in LNCaP‐E9 Cells

Abstract: We previously characterized LNCaP-E9, a low-androgen-sensitive LNCaP cell subline. LNCaP-E9 cells exhibit lower expression of androgen-regulated genes, including prostate-specific antigen (PSA), FK506 binding protein 5 (FKBP5), and prostatic acid phosphatase (PAcP), compared with LNCaP cells after treatment with the synthetic androgen R1881, confirming that the cells have low sensitivity to androgens. To understand the mechanism underlying low androgen sensitivity of LNCaP-E9 cells, we examined the activities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 16 publications
0
9
1
Order By: Relevance
“…We found that VEGF secretion from IL‐6‐treated PCa cells was regulated by the PI3K/AKT signaling pathway. We have recently reported that the low level of Akt phosphorylation was associated with the androgen‐low sensitivity of E9 cells . It is usual that responses to IL‐6 treatment may depend on the different content of membrane IL‐6Rs in PCa cells, although our results showed that responses to IL‐6 treatment on VEGF secretion might be dependent on the level of cellular PI3K/AKT signaling.…”
Section: Discussioncontrasting
confidence: 56%
“…We found that VEGF secretion from IL‐6‐treated PCa cells was regulated by the PI3K/AKT signaling pathway. We have recently reported that the low level of Akt phosphorylation was associated with the androgen‐low sensitivity of E9 cells . It is usual that responses to IL‐6 treatment may depend on the different content of membrane IL‐6Rs in PCa cells, although our results showed that responses to IL‐6 treatment on VEGF secretion might be dependent on the level of cellular PI3K/AKT signaling.…”
Section: Discussioncontrasting
confidence: 56%
“…To find evidence to support this hypothesis, we first employed 3D SIM imaging to evaluate the level of Golgi disorganization. In addition to PC-3 cells, we used high-passage LNCaP cells (c-123), similar to PC-3 in terms of androgen-unresponsiveness (Iguchi, Fukami et al, 2012, Lin, Hu et al, 2003. In low passage LNCaP (c-28) cells, Golgi is consistent with its classical structure and positioning, and virtually no Golgi fragments were observed.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, E9 cells have a more aggressive tumorigenic phenotype than parental LNCaP cells in vivo. We have previously investigated the mechanisms underlying the low androgen sensitivity of E9 cells and found that decreased phosphorylation of Akt was associated with low androgen sensitivity of E9 cells [33]. The Akt and p44/42 MAPK pathways are known to be associated with the regulation of androgen responses [34,35].…”
Section: Discussionmentioning
confidence: 99%